Microbiomic insights into the unique effects of vaginal microbiota on preterm birth in Chinese pregnant women - Zhang, Jun; Xu, Zhimin; Zhang, Mengjun; Fang, Jiaoning; Zheng, Yijing; Jiang, Caihong; Pan, Mian (Frontiers in Microbiology, 2025)
Preterm birth is a major cause of perinatal morbidity and mortality. The disruption of vaginal microbiota in pregnant women is the most significant risk factor for preterm delivery. In this study, 65 pregnant women were enrolled, of which 29 were women with term births and 36 were women with preterm births, and were then categorized based on gestational age at delivery. The results showed that the α-diversity (ACE, Chao1, Simpson, and Shannon indices) of the vaginal microbiota in the term birth group (TG) was significantly higher than that in the preterm birth group (PG). The relative abundance of beneficial bacteria (e.g., Lactobacillus) was significantly reduced in the PG compared to the TG, while the relative abundance of harmful bacteria (e.g., Gardnerella, Atopobium, Ralstonia, and Sneathia) was significantly increased. A prediction model for gestational age at delivery was established based on key microbial phylotypes, and this model was further verified using clinical samples. Statistical analysis revealed that the prediction model utilizing Methyloversatilis, Atopobium, Ralstonia, Sneathia, Brevundimonas, Gardnerella, Acinetobacter, and Peptostreptococcus had higher accuracy. These results suggest that certain bacteria could serve as prospective predictors for preterm birth and provide a theoretical basis for the treatment of preterm birth.